Performing Cultures of Equality - Durán-Almarza, Emilia María; Rodríguez González, Carla; Clisby, Suzanne (Taylor & Francis, 2022)
This book examines the enactment of gendered in/equalities across diverse Cultural forms, turning to the insights produced through the specific modes of onto-epistemological enquiry of embodied performance. It builds on work from the GRACE (Gender and Cultures of Equality in Europe) project and offers both theoretical and methodological analyses of an array of activities and artworks. The performative manifestations discussed include theatre, installations, social movements, mega-events, documentaries, and literary texts from multiple geopolitical locales. Engaging with the key concepts of re-enactment and relationality, the contributions explore the ways in which in/equalities are relationally re-produced in and through individual and collective bodies. This multi- and trans-disciplinary collection of essays creates fruitful dialogues within and beyond Performance Studies, sitting at the crossroads of ethnography, event studies, social movements, visual studies, critical discourse analysis, and contemporary approaches to textualities emerging from post-colonial and feminist studies.